Predictors of Short-Term Changes in Quality of Life after Cochlear Implantation. Issue 3 (14th March 2023) - Walia, Amit; Bao, James; Dwyer, Noel; Rathgeb, Susan; Chen, Stephanie; Shew, Matthew A.; Durakovic, Nedim; Herzog, Jacques A.; Buchman, Craig A.; Wick, Cameron C.
Abstract : Objective: This study aimed 1) to measure the effect of cochlear implantation on health-related quality of life (HR-QOL) using the Cochlear Implant Quality of Life (CIQOL) questionnaire and 2) to determine audiologic, demographic, and non-CI/hearing-related QOL factors influencing the CIQOL. Study Design: Prospective observational study. Setting: Tertiary referral center. Patients and Interventions: Thirty-seven adult patients with sensorineural hearing loss undergoing cochlear implantation. Main Outcome Measure(s): CIQOL-global score preimplantation and 6 months postimplantation. Physical function score as measured by the short-form survey, audiologic, and demographic variables. Results: CIQOL showed significant improvement from preimplantation to 6 months postactivation with a mean difference of 14.9 points (95% confidence interval, 11.3 to 18.5, p < 0.0001). Improvement in CIQOL (ΔCIQOL) correlated linearly with age ( r = −0.49, p = 0.001) and improvement in speech perception testing ( r = 0.63, p < 0.0001). Multivariate modeling using age and change in consonant–vowel nucleus–consonant (CNC) score explained 46% of the variability measured by the ΔCIQOL-global score. Conclusions: Nearly all CI recipients achieve significant gains for all domains as measured by the CIQOL. However, younger patients and those with a greater improvement in speech perception performance (CNC) are more likely to achieve a greater CIQOL benefit. Results here suggest the importance of considering preoperative CIQOL and speech perception measures when evaluating predictors of HR-QOL.